The Influence of Nutritious Food Consumption Patterns in the Free Nutritional Meal Program (MBG) on the Mathematics Learning Achievement of Students at SDS Maniamas Ngabang - Emelia Yesi; Muhammad Firman Annur (Riemann: Research of Mathematics and Mathematics Education, 2025)
This study aims to analyze the effect of the Free Nutritious Meal (Free Nutritious Meal - MBG) program on the mathematics learning achievement of students at SDS Maniamas Ngabang. The research is motivated by a government initiative to address nutritional deficiencies in children, which often impacts the quality of education. This study used a quantitative approach with a pre-experimental one-group pretest-posttest design. Data were collected from 35 students through mathematics achievement tests administered before (pretest) and after (posttest) the implementation of the MBG program. Descriptive statistical analysis showed an increase in the average mathematics learning achievement score from 85.83 to 89.28 after the program was implemented. A paired-sample t-test yielded a significance value (p-value) of 0.000, which is less than 0.05. This result indicates a statistically significant difference between students' learning achievement scores before and after participating in the MBG program. Thus, it can be concluded that the Free Nutritious Meal (MBG) program has a significant positive effect on the improvement of mathematics learning achievement for students at SDS Maniamas Ngabang.